Vision-Related Quality of Life in Iranian Patients With Keratoconus: National Eye Institute Vision Function Questionnaire-25. (November 2018) - Mahdaviazad, Hamideh; Bamdad, Shahram; Roustaei, Narges; Mohaghegh, Sahar
Abstract : Background: Use of patient-reported outcomes to evaluate the impact of ocular conditions on quality of life (QoL) is rising. Hence, the aims of this study were to determine the impact of keratoconus on QoL, and assess the National Eye Institute of the United States Vision Function Questionnaire (NEI-VFQ) performance in an Iranian population. Methods: From November 2016 to June 2017, patients with keratoconus definitive diagnosis for more than one year who were being routinely followed at a cornea clinic were recruited. The NEI-VFQ-25 was administered during a face-to-face interview. Ocular examinations comprised best-corrected visual acuity (BCVA) was logged monocularly and binocularly, anterior segment biomicroscopy, refraction, and corneal topography. Keratoconus severity was graded based on steep keratometric (K) reading values. A group of 30 age- and sex-matched subjects with other ocular diseases (except keratoconus) were selected randomly from the cornea clinic. P <0.05 was considered as significant. Results: The mean age of participants was 28.7±7.6 years. The lowest NEI-VFQ subscale scores were related to ocular pain, general vision, mental health, and role difficulty. Almost all NEI-VFQ scores in patients were statistically significant less than mean score of the control group. Composite and all subscales NEI-VFQ scores were lower significantly among patients with higher disease duration (≥5 years). Among clinical data, patients with BCVA ≥0.5 in the better eye had significantly lower NEI-VFQ composite score. Severe keratoconus patients (steep K reading ≥52) had lower NEI-VFQ scores in mental health and dependency subscales ( P <0.05). The overall and subscales Cronbach α was above 0.7. Conclusion: Iranian patients with keratoconus had physical, emotional, and social impairment in QoL. The NEI-VFQ-25 might be applicable in further studies.